Association of Serum Neurofilament Light Chain Concentration and MRI Findings in Older Adults: The Cardiovascular Health Study. (1st March 2022) - Fohner, Alison E.; Bartz, Traci M.; Tracy, Russell P.; Adams, Hieab H.H.; Bis, Joshua C.; Djousse, Luc; Satizabal, Claudia L.; Lopez, Oscar L.; Seshadri, Sudha; Mukamal, Kenneth J.; Kuller, Lewis H.; Psaty, Bruce M.; et al.
Abstract : Background and Objectives: Neurofilament light chain (NfL) in blood is a sensitive but nonspecific marker of brain injury. This study sought to evaluate associations between NfL concentration and MRI findings of vascular brain injury in older adults. Methods: A longitudinal cohort study included 2 cranial MRI scans performed about 5 years apart and assessed for white matter hyperintensities (WMH) and infarcts. About 1 year before their second MRI, 1, 362 participants (median age 77 years, 61.4% women) without a history of TIA or stroke had measurement of 4 biomarkers: NfL, total tau, glial fibrillary acidic protein (GFAP), and ubiquitin carboxyl-terminal hydrolase L1. Most (n = 1, 279) also had the first MRI scan, and some (n = 633) had quantitative measurements of hippocampal and WMH. In primary analyses, we assessed associations of NfL with a 10-point white matter grade (WMG) and prevalent infarcts on second MRI and with worsening WMG and incident infarct comparing the 2 scans. A p value <0.0125 (0.05/4) was considered significant for these analyses. We also assessed associations with hippocampal and WMH volume. Results: In fully adjusted models, log2 (NfL) concentration was associated with WMG (β = 0.27; p = 2.3 × 10 −4 ) and worsening WMG (relative risk [RR] 1.24; p = 0.0022), but less strongly with prevalent brain infarcts (RR 1.18; p = 0.013) and not with incident brain infarcts (RR 1.18; p = 0.18). Associations were also present with WMH volume (β = 2, 242.9, p = 0.0036). For the other 3 biomarkers, the associations for log2 (GFAP) concentration with WMG and worsening WMG were significant. Discussion: Among older adults without a history of stroke, higher serum NfL concentration was associated with covert MRI findings of vascular brain injury, especially the burden of WMH and its worsening. Whether these results offer opportunities for the use of NfL as a noninvasive biomarker of WMH or to control vascular risk factors remains to be determined.